Acetate favors more phosphorus accumulation into aerobic granular sludge than propionate during the treatment of synthetic fermentation liquor. (August 2016) - Cai, Wei; Huang, Wenli; Li, Huifang; Sun, Beina; Xiao, Huasheng; Zhang, Zhenya; Lei, Zhongfang
Highlights: Ra- and Rp-granules were compared with respect to P recovery and bioavailability. Larger and more stable aerobic granules were achieved by mainly feeding acetate. Higher P removal capability and anaerobic P release were detected in Ra-granules. More cations were accumulated in Ra-granules while more organics in Rp-granules. More GAOs were found to exist in granules fed with propionate. Abstract: Anaerobic digestion (AD) is an efficient biotechnology widely applied for energy and resource recovery from organic waste and wastewater treatment. The effluent from AD or fermentation liquor containing organic substances like volatile fatty acids (VFAs) and mineral nutrients (such as N and P), however, will trigger serious environmental issues if not properly dealt with. In this study two identical sequencing batch reactors (SBRs), namely Ra and Rp were used to cultivate aerobic granules for P recovery from synthetic fermentation liquor, respectively using acetate and propionate as additional carbon source. Larger and more stable granules were achieved in Ra with higher P removal capability (9.4 mg P/g-VSS·d) and higher anaerobic P release (6.9 mg P/g-VSS·h). In addition to much higher P content (78 mg P/g-SS), bioavailable P in Ra-granules increased to 45 mg P/g-SS, approximately 2-times those of seed sludge and Rp-granules. Microbial community analysis indicated that more GAOs were accumulated in Rp-granules.